An in vitro study of orthosiphon stamineus (misai kucing) standardized water extract as a chemolytic agent in urolithiasis - Muhammad Bala Ambursa; Mohd Nor Gohar Rahman; Siti Amrah Sulaiman; Andee Dzulkarnaen Zakaria; Mohamed Ashraf Mohamed Daud; Zaidi Zakaria; Zalina Zahari; Michael Pak-Kai Wong (Wolters Kluwer Medknow Publications, 2021)
Background: Orthosiphon stamineus was reported to have diuretic effects in experimental rats, and this leads to inhibition of kidney stones through the abundant levels of minerals and flavonoids in it. This study aimed to determine the in vitro effects of O. stamineus water extract as a potential chemolytic agent in urolithiasis. Materials and Methods: In this prospective experiment, a total of 15 stone samples collected from patients who underwent stone extraction were used in each concentration (4 mg/ml, 2 mg/ml, and 1 mg/ml) of the O. stamineus extract and control solution. The effects of pH change in the chemolysis of the stones were assessed using the O. stamineus extract 4 mg/ml under pH 7 and 8. Results: The percentage weight reduction of calcium oxalate stone was highest in the 4 mg/ml concentration. O. stamineus extract 4 mg/ml showed a better effect in terms of chemolytic action on calcium oxalate stone than the potassium citrate solution (70% vs. 41%). Regarding the calcium oxalate stone, the percentage weight reduction has shown about 70% in the pH 5, 48% in pH 7, and <10% in pH 8. The percentage weight reduction of uric acid stone was determined as 47%, 11%, and 14% for pH 5, 7, and 8, respectively. The percentage weight reduction of combination stone was 40%, 60%, and 80% in the pH 5, pH 7, and pH 8, respectively. Data analysis showed that the percentage weight reduction of combination stone was significantly different between acidic, neutral, and alkaline conditions (P = 0.027). Conclusions: In this in vitro study, we are able to show that O. stamineus water extract do have some dissolving capability of urinary stones.